Evaluation of the genomic scores of Limousin candidate bulls by cluster analysis - Tőzsér, János; Fazekas, Natasa; Szűcs, Márton (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
The production of purebred Limousin candidate bulls (n = 40) were analysed between 2018-2020. Candidate bulls were kept in small groups (2-9) at the test station, fed with meadow hay, alfalfa ad libitum and dosed fodder. Traits studied were the following: finishing live weight, daily weight gain during the test (g/day) and and genomic scores (GS) for 8 traits (ex: easy calving, vigor of growth, musculatity, score). Data was analysed by SPSS 24.0 software package (K-means cluster analysis). The animals grouped into the first cluster (n=5) showed high growth capacity and excellent growth intensity with good frame size, but at the same time with slightly less favorable bone fineness. The frame size of the individuals belonging to the second and third groups (n=19, n=16) is not outstanding, however, their bone fineness is remarkable. Applying of the K-means cluster analysis can provide the breeders fast and useful information.
Keywords: Limousin candidate bulls; central performance test station; genomic scores; K-means cluster analysis